The process of CPC encouraging enforce behaviour of ethics / Nurlina binti Haridan and Dr. Hafizah binti Mohd Latif - Haridan, Nurlina; Mohd Latif, Hafizah (2018)
A Certificate of Practical Completion (CPC) marks the point at which the contractor has completed the contractual obligation and can hand over the works to client. The aim of this research is to focus on getting Certificate of Practical Completion (CPC) to gives up possession of the site to client as if the client becomes the “building owner” which responsible for insurance, security and maintenance. Throughout getting CPC, rectifying defects commented defect checklist by Clerk of Work (COW) during Pre-Delivery Inspection (PDI) was carried out to minimize defect when client takes possession. At the same time, these action minimized defect works when Defect Liability Period (DLP) begins. During the rectifying the defects, transparency and accountability must be includes to achieves the integrity in Project Management. Data were collected from three case studies through observation, interviews, and documentary evidence. Furthermore, site walk for CPC inspection was held a few times, since the contractor does not satisfied the Client in many aspects due to the pending work. It was found that, Certificated of Practical Completion (CPC) could not achieve if Liability for liquidated damaged is not complete.